“Ante Altaria”: Les Rites antiques de la messe dominicale en Gaule, en Espagne et en Italie du Nord. By Matthieu Smyth - Jeanes, Gordon P. (The journal of theological studies, 2008)
The eucharistic rites of (Mozarabic) Spain, (Gallican) Gaul, and (Milanese) northern Italy, besides being described together as Gallican, are often defined negatively as the ‘non-Roman western rites’, a symptom perhaps of their obscurity compared with the Roman rite itself and the much-discussed eastern rites. In due course they were all but eclipsed by the Roman rite as it changed from being the tradition of the city and its environs to becoming the standard text of western Christendom. Surviving Gallican liturgical documents often display considerable Roman influence, which can make it difficult to appreciate the true nature of the tradition.